Content is King: The Economic Impact of Powerful Narratives in Driving Brand Engagement and Consumer Value - Octavia, Ria; Derina Yusda, Desi; Indriyani, Susi; Meidasari, Evi; Silvia, Dewi (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the impact of a powerful narrative on brand engagement among Tokopedia users, focusing on the mediating roles of customer perception and content engagement. Using a quantitative research design and structural equation modeling (SEM) via Smart PLS, data were collected from 150 management students in Bandar Lampung who use the Tokopedia platform. The findings reveal that emotional engagement and message consistency significantly enhance the perception of a powerful narrative, which in turn positively influences customer perception and content engagement. Both customer perception and content engagement serve as critical mediators, amplifying the narrative's effect on brand engagement. These results suggest that a well-crafted narrative, reinforced by emotional resonance and message consistency, can deepen customer loyalty and advocacy by fostering favorable perceptions and active engagement with brand content. This study highlights the importance for e-commerce platforms like Tokopedia to leverage emotionally engaging and consistent narratives to enhance customer relationships and secure a competitive advantage in digital markets.